2016
DOI: 10.1051/meca/2016065
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of formation of multi-layered coatings for carbide cutting tools

Abstract: -In this paper, we consider the development of the methodology for the formation of nanostructured multi-layered composite coatings to improve the cutting properties of carbide cutting tools in the high-performance machining of various materials. The methodology for the formation of the composition, structure, and properties of developed composite coatings with a three-layered architecture was based on the phenomenological theory of the thermodynamic criteria for the evaluation of adhesion, and the assumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…For deposition of NMCC, a vacuum-arc VIT-2 unit was used, which was designed for the synthesis of coatings on substrates of various tool materials. The unit was equipped with an arc evaporator with filtration of vapor-ion flow, which was named filtered cathodic vacuum-arc deposition (FCVAD) in this study [36][37][38][39], and were used for deposition of coatings on tools to significantly reduce the formation of the droplet phase during the formation of coating. The use of the FCVAD process does not cause structural changes in carbide and provides:…”
Section: Deposition Methodsmentioning
confidence: 99%
“…For deposition of NMCC, a vacuum-arc VIT-2 unit was used, which was designed for the synthesis of coatings on substrates of various tool materials. The unit was equipped with an arc evaporator with filtration of vapor-ion flow, which was named filtered cathodic vacuum-arc deposition (FCVAD) in this study [36][37][38][39], and were used for deposition of coatings on tools to significantly reduce the formation of the droplet phase during the formation of coating. The use of the FCVAD process does not cause structural changes in carbide and provides:…”
Section: Deposition Methodsmentioning
confidence: 99%
“…A special process filtered cathodic vacuum-arc deposition [23][24][25] was used. Table 3 presents the parameters of the process of deposition of coatings.…”
Section: Methodsmentioning
confidence: 99%
“…As with the previous coating, the addition of aluminum and niobium increases the hardness and wear resistance, respectively, while providing greater impact toughness and heat resistance. Based on the previous studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], coating thicknesses of 4-5 mm were assumed as optimal for turning of steels.…”
Section: Methodsmentioning
confidence: 99%
“…Their results showed that the hardness and tensile strength increases with the increase in the weight percentage of SiCp particles. Grigoriev and Vereshchaka [31] studied the methodology of formation of multilayer coatings for carbide cutting tools. Similarly, Gangil et al [32] studied the influence of shoulder geometries and tool pin on microstructure of friction stir processed AA6063/SiC composites.…”
Section: Literature Reviewmentioning
confidence: 99%